Effect of antioxidant dietary behaviour in smokers with chronic obstructive pulmonary disease risk during COVID-19 pandemic - Lorensia, Amelia; Suryadinata, Rivan Virlando (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
Background: Smokers are at risk of Chronic obstructive pulmonary disease (COPD)which has a risk of decreasing in quality of life because of lung function decline and smoking habits. Decreased lung function due to an increase in free radicals. Intake of foods that contain antioxidants can help reduce free radicals.Objectives: The research aimed to determine the effect of antioxidant intake (vitamins A, C, and E) on the development of COPD risk in active smokers.Methods: This study was conducted in May-July 2023 in Surabaya. This study used a cross-sectional design, with purposive sampling and snowball sampling methods. The subjects were adult active smokers. Antioxidant intake consisted of the intake consumed by subjects daily containing vitamins A, vitamin C, and vitamin E using the Food Frequency Questionnaire (FFQ) method to describe nutritional intake in a certain period. COPD risk assessment was measured using a pulmonary function test with spirometry, with an assessment of the ratio of forced expiratory volume in one second (FEV1) / forced vital capacity (FVC) below 0.70 defined as airflow limitation. The data were tested using the Spearman test to see the relationship between antioxidant intake from food and lung function.Results: This study involved 49 active smokers with COPD. Most subjects experienced deficiencies in vitamin A (77.55%), and vitamin C (87.76%), and all subjects experienced vitamin E deficiencies. The most consumed food containing vitamin A was palm oil, the most consumed food containing vitamin C was papaya, and the most consumed food containing vitamin E was chicken. There was no relationship between vitamin A and the development of COPD risk (Sig.=0.187; r=-0.192), but there was a significant relationship (weak negative) between vitamin C and the risk of developing COPD (Sig.=0.031; r=-0.309). All subjects had a deficiency of vitamin E.Conclusions: The lower the intake of vitamin C, the greater the risk of COPD which is characterized by decreased lung function.